2010
DOI: 10.1016/j.blre.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary haemorrhagic telangiectasia: Pathophysiology, diagnosis and treatment

Abstract: Hereditary haemorrhagic telangiectasia, inherited as an autosomal dominant trait, affects approximately 1 in 5,000 people. The abnormal vascular structures in HHT result from mutations in genes (most commonly endoglin or ACVRL1) whose protein products influence TGF-ß superfamily signalling in vascular endothelial cells. The cellular mechanisms underlying the generation of HHT telangiectasia and arteriovenous malformations are being unravelled, with recent data focussing on a defective response to angiogenic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
462
0
29

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 439 publications
(497 citation statements)
references
References 198 publications
(287 reference statements)
6
462
0
29
Order By: Relevance
“…9,10 The signs of HHT may go unrecognized and untreated for decades or cause premature death. 11 A recent study from Italy involving 112 HHT patients who were index cases in their families reported that the mean age at which symptomatic disease manifested was 16.2 years, the mean age of referral for evaluation of those symptoms was 31.7 years, and the mean age of diagnosis of HHT was 45.9 years, for a mean delay of almost 30 years between onset of symptoms and diagnosis. 12 HHT is associated with significantly higher rates of premature mortality before 60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The signs of HHT may go unrecognized and untreated for decades or cause premature death. 11 A recent study from Italy involving 112 HHT patients who were index cases in their families reported that the mean age at which symptomatic disease manifested was 16.2 years, the mean age of referral for evaluation of those symptoms was 31.7 years, and the mean age of diagnosis of HHT was 45.9 years, for a mean delay of almost 30 years between onset of symptoms and diagnosis. 12 HHT is associated with significantly higher rates of premature mortality before 60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] In contrast, for PAVM patients, the absence of alveolar hypoxia/hypoxic pulmonary vasoconstriction, and PAVM-related structural alterations in the pulmonary vessels, mean that pulmonary vascular resistance at rest is low in severely hypoxemic patients. 3,6,7 The majority of PAVM patients have underlying hereditary hemorrhagic telangiectasia(HHT), 11,17,18 but overall, pulmonary hypertension is uncommon in PAVM/HHT patients. 12 When pulmonary hypertension does occur, 19,20 this results not from hypoxia, but from other pathophysiological processes, particularly pulmonary arterial hypertension, 12,[21][22][23][24] and pulmonary venous hypertension associated with hepatic AVMs and high outputs states.…”
Section: ṽO2mentioning
confidence: 99%
“…HHT patients present with recurrent nosebleeds and develop cutaneous and mucosal blood vessel dilatations. Some patients also develop life-threatening arteriovenous malformations (25). HHT can be caused by mutations in other ALK-1 pathway components, including the ALK-1 coreceptor endoglin that aids ligand binding, and Smad4, which partners with TGF-β-and BMP-activated Smads (25).…”
mentioning
confidence: 99%
“…Some patients also develop life-threatening arteriovenous malformations (25). HHT can be caused by mutations in other ALK-1 pathway components, including the ALK-1 coreceptor endoglin that aids ligand binding, and Smad4, which partners with TGF-β-and BMP-activated Smads (25). Recently, causative BMP9 missense mutations have been implicated in an HHT-related syndrome (26).…”
mentioning
confidence: 99%